A Day At School With The Very Hungry Caterpillar - Roth, Megan; Carle, Eric (New York : World of Eric Carle, 2023)
The Very Hungry Caterpillar spends a busy day at school from greeting the teacher to reading a book.
Cover title.
On board pages with die-cut tabs.
new kids book 2025 summer.
Ages 1-3.
Keywords: Board books; Toy and movable books -- Specimens; Caterpillars -- Fiction; Schools -- Fiction; Board books; Toy and movable books; Toy and movable books; Board books; Picture books